2007
DOI: 10.1016/j.gene.2007.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The MADS-domain protein PPM2 preferentially occurs in gametangia and sporophytes of the moss Physcomitrella patens

Abstract: To date, the function of MADS-domain transcription factors in non-seed plants remains largely elusive, although a number of genes have been isolated and characterized from a variety of species. In our study we analyzed PPM2, a classical MIKC-type MADS-box gene from the moss Physcomitrella patens, taking advantage of the unique technical properties Physcomitrella offers in terms of efficient homologous recombination. We determined mRNA and protein distribution and performed targeted disruption of the genomic lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Comparative studies between P. patens and Arabidopsis have indicated that the consecutive evolution of this new structure involved the modification of sporophytespecific developmental programs (Maizel et al 2005;Tanahashi et al 2005), as well as a recruitment of gametophytic developmental programs into the sporophytic generation (Nishiyama et al 2003;Menand et al 2007). MIKC c MADS-box genes seem to have largely undergone the latter fate because they are expressed in both the gametophyte and the sporophyte in mosses and ferns (Munster et al 1997;Hasebe et al 1998;Quodt et al 2007) and almost exclusively in the sporophyte in Arabidopsis (Kofuji et al 2003). On the other hand, our data suggest that MIKC* MADS-box genes have generally retained a role in the gametophytic generation of land plants.…”
Section: Evolutionary Diversification Of the Mikc* Mads-box Gene Cladementioning
confidence: 69%
“…Comparative studies between P. patens and Arabidopsis have indicated that the consecutive evolution of this new structure involved the modification of sporophytespecific developmental programs (Maizel et al 2005;Tanahashi et al 2005), as well as a recruitment of gametophytic developmental programs into the sporophytic generation (Nishiyama et al 2003;Menand et al 2007). MIKC c MADS-box genes seem to have largely undergone the latter fate because they are expressed in both the gametophyte and the sporophyte in mosses and ferns (Munster et al 1997;Hasebe et al 1998;Quodt et al 2007) and almost exclusively in the sporophyte in Arabidopsis (Kofuji et al 2003). On the other hand, our data suggest that MIKC* MADS-box genes have generally retained a role in the gametophytic generation of land plants.…”
Section: Evolutionary Diversification Of the Mikc* Mads-box Gene Cladementioning
confidence: 69%
“…Given the ubiquitous presence of MADS-box genes in embryophytes together with what we know already about their important roles in the development and evolution of spermatophytes, it is clear that we should now afford a high priority to functional analyses of the complete MADS-box gene complement discerned within the S. moellendorffii genome. It will be interesting to discover, for example, whether any of the S. moellendorffii genes encode a reproductive function as has been shown for some MIKC C genes in P. patens (Quodt et al, 2007; Singer et al, 2007) and appears likely for charophycean algae (Tanabe et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, BELL1 might play a role in male fertility in P. patens. MADSbox genes are important for flower, pollen and fruit development (Theißen et al 2016) and have previously been associated with sexual reproduction in P. patens (Hohe et al 2002, Quodt et al 2007, Singer et al 2007. P. patens MIKC c -type genes are important for motile flagella and external water conduction (Koshimizu et al 2018).…”
Section: Rna-seq Of Male Reproductive Organs Suggests Differential Trmentioning
confidence: 99%